Viver mais é viver melhor?: Uma análise da esperança de vida feliz no Brasil - Luisa Pimenta Terra (2010)
One of the most important achievements of the society in the last centuries is the rapid increase in life expectancy at birth. The debate today is whether those additional years of life are lived in good quality. This masters´ thesis contributes to this literature using self-perception of happiness as a measure of life quality. In general, health related measures are used as indicators of well-being, but the results are affected by the definition of health proposed by the researchers and are limited because they do not capture the effect of other domains in the individual well-being. Happiness is considered one of the best indicators of quality of life (Graham, 2008; Veenhoven, 1997; Yang, 2008) and encompasses different aspects such as physical and mental health, economic conditions and employment mainly their effect on the life of each individual.Data from the 1997 and 2006 World Values Survey and IBGE Life Tables are used to estimate happy life expectancy for males and females in Brazil using Sullivan´s method. We find an absolute increase in happy life expectancy and that proportion of life lived in happiness has also increased for both sexes. The results indicate a process of compression of unhappiness. We also found that happy life expectancy increases faster than healthy life expectancy and life expectancy on satisfaction, and that life expectancy in satisfaction is longer than healthy life expectancy. The results also show that individuals in poor health and dissatisfied with life have long years of happy life. We also find that the compression of unhappiness is greater than the compression of morbidity, especially for women and for adult males Finally, there are important and significative differences by sexes in all measures, The proportion of life lived in happiness is greater than the female for all age groups and both periods. But the difference seems to be reducing over time.